(3CUhd GdCMSGH haUhd GdCfSGHs - (3GdLhGfj , TQa GdOjf CHh Ydj eMeO Hf CSYO Hf Ydj Hf eYeQ GdTQja GdMSjfj GdYdhj GdYHjOj GdeGdcj, GdLhGfj,J (B588 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Hjf GdCee HHjGf QShdg eMeO SjO GdYQH hGdYLe , eG ajg ENJdahG gPg JMaI XQjaI hebOeI dWjaI hgOjI efjaI ai CUhd GdCMSGH haUhd GdCfSGH Ef LejY eG HfJ Ydjg GdYQH ai fSHgG s
(3BNQgG (B:s
(3hGdYbH ef QheGf Hf LfOH Hf NGQLI Hf SYO Hf aWQ ef HWfjf Pgd hKYdHI hgeG GdKYdHjGf hLeGYI UZGQ hGdYbH ef GdZhK Hf WF Hf COO Hf RjO ef YeQh Hf GdZhb hGdYbH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B49s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B451 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B626 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs